Representation of Patriarchy in Sasti Gotama's Novel Corpus Uterus: A Study of Kate Millet's Radical Feminism: - Dinda Sabrina Iskandar; Resdianto Permata Raharjo (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the representation of patriarchy in Sasti Gotama’s novel “Corpus Uterus” thru the perspective of Kate Millett’s radical feminism. This research was conducted on novel texts as the object of study, with the research period from October to December 2025. The research data consists of narrative quotes, dialog, and character descriptions that represent patriarchal practices in the lives of the female characters. Data collection was carried out using the read and note technique with intensive text reading. Data analysis was performed using a descriptive qualitative approach thru intensive reading, data grouping, and interpretation of meaning based on Kate Millett’s radical feminist framework. The research findings indicate that patriarchy in the novel is represented thru eight aspects: biological, ideological, sociological, class, economic and educational, coercion, myths and religion, and psychological. Patriarchy systematically works to limit women’s bodies, social roles, and the autonomy of female figures thru unequal power relations. Some of the female characters in this novel, particularly Kalimah, experience role limitations, violence, and psychological pressure as a result of the patriarchal system deeply rooted in social and cultural structures. This finding shows that women’s personal experiences in the novel are not separate from the patriarchal power structure that places women in a subordinate position. Thus, the novel Corpus Uterus represents patriarchy as a deeply rooted system that has a direct impact on women’s lives and experiences.